2017
DOI: 10.3762/bjoc.13.86
|View full text |Cite
|
Sign up to set email alerts
|

First total synthesis of kipukasin A

Abstract: In this paper, a practical approach for the total synthesis of kipukasin A is presented with 22% overall yield by using tetra-O-acetyl-β-D-ribose as starting material. An improved iodine-promoted acetonide-forming reaction was developed to access 1,2-O-isopropylidene-α-D-ribofuranose. For the first time, ortho-alkynylbenzoate was used as protecting group for the 5-hydoxy group. After subsequent Vorbrüggen glycosylation, the protecting group could be removed smoothly in the presence of 5 mol % Ph3PAuOTf in dich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Because only small amount of nucleoside 1 was isolated, its biological activity was not reported by the authors. As our continuous study on total synthesis of naturally occurring nucleosides, we started to carry out its synthesis and investigate its biological activities [12][13][14][15][16][17]. From the synthetic point view, synthesis of β-L-arabinosyluridine could be carried out in two different approaches shown in Figure 2.…”
Section: Examination the Chemical Structures Of All Reported Naturallmentioning
confidence: 99%
“…Because only small amount of nucleoside 1 was isolated, its biological activity was not reported by the authors. As our continuous study on total synthesis of naturally occurring nucleosides, we started to carry out its synthesis and investigate its biological activities [12][13][14][15][16][17]. From the synthetic point view, synthesis of β-L-arabinosyluridine could be carried out in two different approaches shown in Figure 2.…”
Section: Examination the Chemical Structures Of All Reported Naturallmentioning
confidence: 99%
“…Due to the above-mentioned reasons and our continuing effort to synthesize bioactive marine nucleosides [20,21,22,23,24,25,26,27], we are interested in the total synthesis and structure-activity relationship studies of 4′,5′-unsaturated 7-deazapurine nucleosides as antibiotics. A literature search revealed that the first total synthesis of mycalisine A was accomplished using toyocamycin as a starting material shortly after it was reported [28].…”
Section: Introductionmentioning
confidence: 99%